Realistic Model-Based Learning and Motor Satisfaction in Futsal Skills: Pembelajaran Berbasis Model Realistis dan Kepuasan Motorik dalam Keterampilan Futsal - Khamees, Imad Mohsin (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Traditional teaching methods in physical education often fail to create meaningful learning experiences. Specific Background: The realistic model emphasizes contextual and experiential learning, allowing students to apply technical skills in game-like settings. Knowledge Gap: Few studies have examined how realistic model-based learning affects motor satisfaction and skill acquisition in futsal. Aims: This study aimed to evaluate the effect of educational units based on the realistic model on motor satisfaction and the learning of rolling and scoring skills among students. Results: Findings revealed significant improvements in both motor satisfaction and performance accuracy for the experimental group compared with the control group. Novelty: The study introduces the realistic model as an effective pedagogical framework for futsal education. Implications: Implementing this model can improve motivation, engagement, and technical learning outcomes in school-level physical education programs. Highlights:• Realistic model-based learning enhances students’ motor satisfaction.• Significant improvement was observed in rolling and scoring skills.• The study supports experiential learning as a framework for sports education. Keywords:Realistic Model, Motor Satisfaction, Futsal, Skill Learning, Experiential Teaching